Nasal CPAP and weight loss in hypertensive patients with obstructive sleep apnoea. Issue 5 (May 1993) - Rauscher, H; Formanek, D; Popp, W; Zwick, H
Abstract : BACKGROUND–The high prevalence of obstructive sleep apnoea (OSA) in patients with systemic hypertension and of hypertension in patients with OSA suggests a causal link between the two disorders. This study was carried out to determine whether nasal continuous positive airway pressure (CPAP) and weight loss affect daytime hypertension in OSA. METHODS–Sixty hypertensive patients with OSA took part in the study; 33 accepted nasal CPAP and used their machine for 5.7 (0.2) hours per night, and the remaining 27 patients refused nasal CPAP and upper airway surgery so the only therapeutic intervention was a recommendation of weight loss. A significant change in hypertension during follow up was defined as either a change in mean blood pressure of at least 10 mm Hg (or more than 8%) without a change in drug treatment, or a reduction in drug dosage with mean blood pressure within these limits. Weight loss was defined as a body mass index of at least 5% below the baseline value. RESULTS–After 512 (41) days, hypertension had become less severe in seven of 12 patients (58%) treated with weight loss only, in eight of 28 patients (29%) with nasal CPAP only, in two of five patients with nasal CPAP and weight loss, and in one of 15 patients without nasal CPAP or weight loss. Multivariate analysis of variance with the outcome of hypertension at follow up as the dependent variable revealed that only the percentage change in body mass index significantly contributed to the course of hypertension. CONCLUSION–The course of hypertension in OSA is more closely linked to weight loss than to elimination of sleep apnoea by nasal CPAP.